Relationship between 25-hydroxy vitamin D and knee osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Wang, Rui; Wang, Zheng-ming; Xiang, Si-cheng; Jin, Zhao-kai; Zhang, Jing-jing; Zeng, Ji-cheng; Tong, Pei-jian; Lv, Shuai-jie (Frontiers in Medicine, 2023)
Objective In order to examine the relationship between 25-hydroxyl vitamin D and knee osteoarthritis (KOA), a meta-analysis of 8 randomized controlled trials (RCTs) publications was hereby performed. Methods For the purpose of finding pertinent research, the databases of PubMed, Embase and the Cochrane Library were searched. Factors including tibial cartilage volume, joint space width (JSW), synovial fluid volume, and Western Ontario and McMaster Universities Arthritis Index (WOMAC) were correspondingly evaluated, and the results were expressed using SMD and 95% confidence intervals (CI). Results The present meta-analysis evaluated the effects of vitamin D supplementation in patients with knee osteoarthritis, with 3,077 patients included. The results showed that vitamin D administration had a statistically significant impact on the amount of synovial fluid, Visual Analog Scale (VAS) and tibial cartilage. The pain and function scales of the WOMAC scale presented a statistically significant difference, and there was no discernible difference between the vitamin D and placebo groups in the stiffness scale. Additionally, bone marrow lesions and alterations in the diameter of the joint space were not influenced by the administration of vitamin D, and according to a subgroup study, a daily vitamin D supplement containing more than 2,000 IU significantly slowed the development of synovial tissue. Conclusion Vitamin D supplementation did benefit those suffering from knee discomfort and knee dysfunction. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022332033, identifier: CRD42022332033.